Anterior abdominal wall spindle cell tumour - atypical fibrous histiocytoma: a rare presentation - ., Shubham; Ravi, Ashokan; S. J., Haridarshan (International Surgery Journal, 2018)
Atypical fibrous histiocytoma is a rare and a distinct variant of cutaneous fibrous histiocytoma which can be misdiagnosed as sarcoma. It is mainly composed of a mixture of fibroblastic and histiocytic cells, especially found in the skin (dermatofibroma), particularly in the limbs. It is quite uncommon and is difficult to distinguish from a malignant lesion. Due to the lack of clear cut predictive morphological patterns and due to the suspicion of malignancy, complete surgical excision is recommended. Provided that atypical fibrous histiocytoma is treated by complete excision, a benign outcome is to be expected in most cases. However, like the cellular and aneurysmal variants of fibrous histiocytoma, atypical fibrous histiocytoma shows a higher tendency to recur locally than ordinary fibrous histiocytoma and may rarely metastasize. Lesions with floridly atypical features represent potential pitfalls for overinterpretation as pleomorphic sarcoma, which would appear to be inappropriate in most cases. Due to its rarity and uncertainty, we report a case of atypical fibrous histiocytoma and discuss its presentation, nature, types and treatment with reference to a brief review of literature.